Records needed for orthodontic diagnosis and treatment planning: a systematic review. - Robine J Rischen; K Hero Breuning; Ewald M Bronkhorst; Anne Marie Kuijpers-Jagtman (PLoS ONE)
Background Traditionally, dental models, facial and intra-oral photographs and a set of two-dimensional radiographs are used for orthodontic diagnosis and treatment planning. As evidence is lacking, the discussion is ongoing which specific records are needed for the process of making an orthodontic treatment plan. Objective To estimate the contribution and importance of different diagnostic records for making an orthodontic diagnosis and treatment plan. Data sources An electronic search in PubMed (1948-July 2012), EMBASE Excerpta Medica (1980-July 2012), CINAHL (1982-July 2012), Web of Science (1945-July 2012), Scopus (1996-July 2012), and Cochrane Library (1993-July 2012) was performed. Additionally, a hand search of the reference lists of included studies was performed to identify potentially eligible studies. There was no language restriction. Study selection The patient, intervention, comparator, outcome (pico) question formulated for this study was as follows: for patients who need orthodontic treatment (P), will the use of record set X (I) compared with record set Y (C) change the treatment plan (O)? Only primary publications were included. Data extraction Independent extraction of data and quality assessment was performed by two observers. Results Of the 1041 publications retrieved, 17 met the inclusion criteria. Of these, 4 studies were of high quality. Because of the limited number of high quality studies and the differences in study designs, patient characteristics, and reference standard or index test, a meta-analysis was not possible. Conclusion Cephalograms are not routinely needed for orthodontic treatment planning in Class II malocclusions, digital models can be used to replace plaster casts, and cone-beam computed tomography radiographs can be indicated for impacted canines. Based on the findings of this review, the minimum record set required for orthodontic diagnosis and treatment planning could not be defined. Systematic review registration number CRD42012002365.